CYP2C19*1 and CYP2C19*2 Polymorphism in Turkish Patients Being Diagnosed with Stable Coronary Artery Disease and Using Clopidogrel - Ramazan Sabırlı; Aylin Köseler; Atakan Yılmaz; İsmail Doğu Kılıç (Bagcilar Medical Bulletin, 2021)

(untitled)
Objective:The CYP2C19*1 has an entirely normal activity allele whose clopidogrel metabolism is normal. CYP2C19*2 called as non-functional alleles. In this study, we aimed to establish the CYP2C19*1 and CYP2C19*2 genotype frequencies both in Turkish patients with coronary artery disease (CAD), who used clopidogrel, and in healthy Turkish population as well as to present the differences in genotypes and alleles between both groups.Method:One hundred healthy individuals and 200 patients diagnosed with CAD were included in the study. DNA was isolated and CYP2C19 gene was amplified through the polymerase chain reaction method in the genomic DNAs obtained, and the polymorphic foci in these regions were specified.Results:CYP2C19*1/1 genotype was identified in 132 patients (66%), CYP2C19*1/2 genotype in 62 patients (31%) and CYP2C19*2/2 genotype in 6 patients (3%) in the CAD group. In the control group, by contrast, 72 patients (72%) were identified with CYP2C19*1/1 genotype, 20 patients with CYP2C19*1/2 genotype and 8 patients with CYP2C19*2/2 genotype. There was a significant difference between the groups in terms of genotypes (p=0.034).Conclusion:We found CYP2C19*1/2 and CYP2C19*2/2 genotype to be higher in the CAD patients than in the control group, highlighting the importance of checking CYP2C19 gene polymorphism prior to the initiation of antiplatelet therapy in CAD patients.